2011
DOI: 10.1063/1.3532110
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced critical temperature in epitaxial ferroelectric Pb(Zr0.2Ti0.8)O3 thin films on silicon

Abstract: The structural and electrical properties of epitaxial Pb͑Zr 0.2 Ti 0.8 ͒O 3 thin films grown on 2 in. ͑001͒ silicon wafers were investigated. Using x-ray diffraction, the lattice behavior of the heterostructure has been studied as a function of temperature, suggesting a 250°C increase of the Pb͑Zr 0.2 Ti 0.8 ͒O 3 ferroelectric-paraelectric transition temperature with respect to the bulk value. This significant enhancement of the critical temperature is understood in terms of a two-dimensional clamping effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…5(a)] leads to the decrease of remnant polarization [Fig. 5(b)] 29 , which is responsible for the pyroelectricity 5,23 . The variation of the polarization with temperature should be larger along the main polarization and the largest tetragonality [Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5(a)] leads to the decrease of remnant polarization [Fig. 5(b)] 29 , which is responsible for the pyroelectricity 5,23 . The variation of the polarization with temperature should be larger along the main polarization and the largest tetragonality [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The variation of the polarization with temperature should be larger along the main polarization and the largest tetragonality [Fig. 5(c)] 12,29 . Even if both the main polarization ( c -axis) and the largest tetragonality lie in-plane here, the OOP pyroelectric response is much larger than the IP pyroelectric response.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…72 , 73 Using radio frequency-magnetron sputter deposition for the growth of SrRuO 3 / Pb(Zr 0.2 Ti 0.8 O 3 ) epitaxial heterostructures on SrTiO 3 buffered Si, Sambri et al reported a remanent polarization of about 70 μ C/cm 2 , with no signifi cant leakage current up to 16 V and a d 33 piezoelectric coeffi cient (this value refers to the geometry where the electric fi eld is applied along the ferroelectric polarization and the displacement is measured along this same axis) from the remanent response, measured by a piezoelectric force microscopy of 50 pm/V for a ferroelectric layer of 100 nm. 74 Here, a 45° rotated cube-on-cube epitaxy of PZT on silicon is found, as schematically depicted in Figure 5c . Using XRD (see …”
Section: Srtio 3 /Sro As a Buff Er Layermentioning
confidence: 95%
“…The major advance of introducing such layer was to prevent the formation of amorphous silicon oxide on the Si surface in order to boost the growth of STO. Since then, STO/Si(001) has been used as a large-scale pseudo-substrate for the integration and development of functional perovskite oxides on Si [5,[22][23][24][25][26]. Following the same philosophy, Yttria-stabilized zirconia (YSZ) grown by PLD has also been used as an effective buffer layer to develop the technology of oxide films on Si(001) [27].…”
Section: Integration Of Functional Oxides By Physical Methodsmentioning
confidence: 99%